Sociocultural Dynamics of Perception of Italian Brands in Russia - R. D. Akinina; A. S. Gonashvili; N. P. Kirsanova (Дискурс, 2021)
Introduction. This article analyzes the specifics of the perception of Italian brands in Russia. The starting point in the paper is the understanding that the evolution of Italian culture and the image of Italy itself has led to the perception of this phenomenon through the prism of both its numerous attributes and Italian brands in particular. Today Italy is associated with national cuisine, culture and historical heritage.From a sociological perspective, brands are an important resource for the representation of national culture, especially for foreign consumers. To date, however, there has been little research into how this culture is transmitted through brands to society. In particular, little attention has so far been paid to studying the perception of brands and their relationship to the national culture of the country they represent.The socio-cultural perspective of the study implies an examination of the dynamics of attitudes towards Italian brands, reflecting the variability of society itself.Methodology and sources. The methodological basis is an interdisciplinary approach to the problem of studying and analyzing brands. The main research method in the work is the Internet survey. Thus, based on the theoretical concepts on the study of brands in sociology, in April 2020 on the platform ”Google Form” the authors conducted an empirical study. The purpose of this research was to conduct an online survey to identify the attitudes of Russian respondents towards Italian brands. The results of the sociological research conducted in the form of a questionnaire survey are presented. The sample type was random with the number of 150 respondents.Results and discussion. According to the survey results, the main associations associated with the image of Italy are: Italian food, holidays, fashion and historical heritage. At the same time, about one fifth of respondents are not familiar with any of the Italian brands or cannot name them. Among those familiar with Italian brands, 80 % responded that they know Gucci, Fendi, Valentino, Versace, Moschino, Giorgio Armani, Prada, Roberto Cavalli, Dolce & Gabbana, Lamborghini, Maserati and Ferrari.One of the key findings of the study was the conclusion that brand perception today is not directly related to its country of origin. The brand does not always represent the country, becoming multicultural. The socio-cultural model of consumption is changing, and the understanding of the Italian brand is divorced from the cultural foundation from which it originated.Conclusion. In general, the authors of the article come to the conclusion that the perception of Italian brands in Russia is conditioned by the specifics of sociocultural development. In the early nineties, when the country had just opened up to Western brands, it was vital for the consumer to purchase products from well-known brands, in particular the «Made in Italy» category, firmly associated with the country of origin. Today, in the context of globalization and multiculturalism, many brands have lost their national identity, and for the consumer the consumer properties of the product come first, and not the brand itself.